Management in Single-Teacher Schools and Dirección 1: A Challenge to Reach Educational Equity in Rural Contexts in Costa Rica - Miranda-Calderón, Luis Alfredo (2018)
Currently, management is one of the main challenges single-teacher schools and principals located in Costa Rican rural contexts have to face in order to achieve equity and educational relevance. The objective of this qualitative-descriptive study is to analyze and strengthen management accomplished by teachers working as single-teachers in schools denominated “Dirección 1” (a single-teacher school category of the Costa Rica Education System), located in rural communities in the Sarapiquí area of Costa Rica. The purpose is to contribute to the improvement of the education in these institutions through the implementation of a training proposal that includes the two main components of their management tasks: the pedagogical aspect and the administrative one. Based on the diagnosis and information provided by 28 managers from the Sarapiquí area (16 from single-teacher schools and 12 from “Dirección 1”) through a questionnaire and a semi-structured interview, the reality of these institutions was examined in depth in order to determine the conditioning situations of administrative management as a requirement of their educational work, as well as the implications for the pedagogical work they carry out. Derived from the reflections and findings of the study, the training and continuing education proposal was generated around topics that each teacher of these institutions must consider fundamental to provide relevance to their educational management. Finally, a set of strategies is proposed to guide and facilitate the execution of administrative procedures developed by each teacher as part of their educational work in the communities where they work.